Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Kemampuan Komunikasi Ilmiah dan Hasil Belajar Fisika Siswa SMA - Oviane Brian Pramesti; Supeno Supeno; Sri Astutik (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2020)
The purpose of this study is to examine the effect of guided inquiry learning models on the ability of scientific communication and physics learning outcomes of class X students at SMAN 1 Gambiran, Banyuwangi. This research is a quasi-experimental research conducted by posttest-only design. The research sample is students of Class X Science 1 as an experimental class and students of Class X Science 2 as a control class with each class having 34 students. The experimental class received treatment in the form of physics learning using the guided inquiry learning model while the control class used the learning model commonly used by teachers at the school. Research data obtained through observation and tests. The data analysis technique used is the t test which was previously tested by data normality. The data obtained shows that the average scientific communication ability of students in the experimental class is greater than the control class, namely 74.5 and 68.2, respectively. The average student learning outcomes in the experimental class were also greater than the control class, namely 69.7 and 58.8, respectively. Statistical test results show that there are differences in scientific communication skills and learning outcomes between experimental class students and control class students so that it can be concluded that the guided inquiry learning model influences the scientific communication skills and physics learning outcomes of high school students.